Collaborative Supply Chain System; Case Study Port East Indonesia - Jimmy Roland Alfius Torar; Delly Mustafa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Supply chain management refers to a set of strategies and commercial operations concerned with the movement of products and services. Planning, providing, creating, and distributing goods and services until they are accepted by customers are examples of these tasks. Supply chain management blends supply and demand management to ensure effective and efficient operation. The purpose of supply chain management is to optimize the time, location, and flow of material quantities to satisfy consumers, decrease costs, and boost the productivity of enterprises in the supply chain. We offer a collaborative logistics framework for a Port Logistics Chain (PLC) based on Supply Chain Management (SCM) concepts that rely on stakeholder integration and cooperation in this paper, giving a reference model for the PLC's inland coordination. A thorough literature analysis was carried out, which included an examination of many situations in which SCM methods were adopted, as well as research on port development, governance, coordination, and best practices. This background information was utilized to identify present gaps in logistics management practices and prospective scopes of intervention inside the PLC in order to recommend a redesign process and construct new structures in accordance with SCM rules.